Toxic effects of subacute exposure to Nerium oleander leaves hexane extract on the heart of rabbits: Ali Aziz Alkhayyat and Rana Abdulla Salih - Salih, Rana Abdulla (The Iraqi Journal of Veterinary Medicine, 2018)
The study is performed to investigate the cardiotoxic effect of two season oleander leave extract in rabbits. The study involved a collection of the Nerium oleander leaves of two seasons (summer and winter) taken from Baghdad. The leaves were prepared by drying and grinding, and the extraction was carried by soxhlet apparatus with organic solvent (hexane). The toxicity was carried out on rabbits by giving 10% of the median lethal dose (LD50) for four weeks by considering different electrocardiography parameters and cardiac histopathological study after two weeks and four weeks of daily treatment. The electrocardiography parameters include R-R duration, T amplitude and Q-T duration values. The results of lead II referred to the heart rate as in R-R duration values which showed significant differences at (P<0.05) in two weeks between digoxin and control group, furthermore non significant increase occurred in all groups compared to control group in different times, and T amplitude revealed a decrease indicative of the levels of potassium in cardiac intracellular were decreased in all groups as compare to control group in different times, and decreased of Q-T duration which indicate calcium levels in cardiac intracellular were increased in all groups as compared to control in different times. Histopathology study of heart muscle in all groups in different times, showed edema, vacuolation, fragment and mononuclear cells infiltration in the pericardium in heart muscle. In conclusion, the N. oleander leaves extract has a toxic effect on the cardiac muscle.